(2x-1)x2y+2y-1=480
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(\dfrac{\left(x+1\right)}{x^2+2x-3}=\dfrac{\left(x+1\right)}{\left(x+3\right)\cdot\left(x-1\right)}=\dfrac{\left(x+1\right)\left(x+2\right)\left(x+5\right)}{\left(x+3\right)\left(x-1\right)\left(x+2\right)\left(x+5\right)}\)
\(\dfrac{-2x}{x^2+7x+10}=\dfrac{-2x}{\left(x+2\right)\left(x+5\right)}=\dfrac{-2x\left(x+3\right)\left(x-1\right)}{\left(x+2\right)\left(x+5\right)\left(x+3\right)\left(x-1\right)}\)
b: \(\dfrac{x-y}{x^2+xy}=\dfrac{x-y}{x\left(x+y\right)}=\dfrac{y^2\left(x-y\right)}{xy^2\left(x+y\right)}\)
\(\dfrac{2x-3y}{xy^2}=\dfrac{\left(2x-3y\right)\left(x+y\right)}{xy^2\left(x+y\right)}\)
c: \(\dfrac{x-2y}{2}=\dfrac{\left(x-2y\right)\left(x-xy\right)}{2\left(x-xy\right)}\)
\(\dfrac{x^2+y^2}{2x-2xy}=\dfrac{x^2+y^2}{2\left(x-xy\right)}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=2x+xy^2-x^2y-2y\)
\(=2\left(x-y\right)-xy\left(x-y\right)\)
\(=\left(x-y\right)\left(2-xy\right)\)
\(=\left(-\dfrac{1}{2}-\dfrac{-1}{3}\right)\left(2-\dfrac{-1}{2}\cdot\dfrac{-1}{3}\right)\)
\(=\left(\dfrac{1}{3}-\dfrac{1}{2}\right)\cdot\left(2-\dfrac{1}{6}\right)\)
\(=\dfrac{-1}{6}\cdot\dfrac{11}{6}=-\dfrac{11}{36}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a,x2-y2-2x+2y
= (x+y)(x-y) - 2(x-y)
= (x-y)(x+y-2)
b,2x+2y-x2-xy
= 2(x+y) - x(x+y)
= (x+y)(2-x)
c,3a2-6ab+3b2-12c2
= 3(a2 - 2ab + b2 - 4c2)
= 3[(a-b)2 - 4c2)
= 3(a-b-2c)(a-b+2c)
d,x2-25+y2+2xy
= (x+y)2 - 25
= (x+y+5)(x+y-5)
e) a2+2ab+b2-ac-bc
= (a+b)2-c(a+b)
= (a+b)( a+b-c)
f) x2-2x-4x2-4y
= -3x2-2x-4y
= -(3x2+2x+4y)
g)x2y-x3-9y+9x
= x2(y-x)-9(y-x)
= (y-x)(x2-9)
h) x2(x-1)+16(1-x)
= x2(x-1)-16(x-1)
= (x-1)(x2-16)
= (x-1)(x-4)(x+4)
n) 81x2-6yz-9y2-z2
= (9x)2-[(3y)2+6yz+z2]
=(9x)2-(3y+z)2
=(9x+3y+z)(9x-3y-z)
m) xz- yz-x2+2xy-y2
= z(x-y)-(x2-2xy+y2)
= z(x-y)-(x-y)2
= (x-y)(z-x+y)
p) x2 + 8x + 15
= x2 + 3x + 5x + 15
= x(x+3) + 5(x+3)
= (x+3)(x+5)
k) x2 - x - 12
= x2 + 3x - 4x - 12
= x(x+3) - 4(x+3)
= (x+3)(x-4)
![](https://rs.olm.vn/images/avt/0.png?1311)
a/ 5x2y (x2y– 4xy2 + 7xy)
`=5x^4y^2-20x^3y^3+35x^3y^2`
b/ 3xy2 (x2y3 + x 2y – xy2 )
`=3x^3y^5+3x^3y^3-3x^2y^4`
c/ 3x(12x2 + 4x – 5) + 2x(9x2 – 6x + 7)
`=36x^3+12x^2-15x+18x^3-18x^2+14x`
`=54x^3-6x^2-x`
d/ 5x(2x2 – 9x – 5) – 9x (x2 - 7x – 4)
`=10x^3-45x^2-25x-9x^3+63x^2+36x`
`=x^3+18x^2+11x`
![](https://rs.olm.vn/images/avt/0.png?1311)
(12x³3y² - 8x²y² - x²y) : 4x²y - 2y(x - 1)
= 9xy - 2y - 1/4 - 2xy + 2y
= 7xy - 1/4
![](https://rs.olm.vn/images/avt/0.png?1311)
1:
Ta có: \(B=2x+xy^2-x^2y-2y\)
\(=\left(2x-2y\right)+\left(xy^2-x^2y\right)\)
\(=2\left(x-y\right)+xy\left(y-x\right)\)
\(=\left(x-y\right)\left(2-xy\right)\)
2:
Ta có: \(C=xy-4y-5x+20\)
\(=\left(xy-4y\right)-\left(5x-20\right)\)
\(=y\left(x-4\right)-5\left(x-4\right)\)
\(=\left(x-4\right)\left(y-5\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, `(8x^3-4x^2): 4x -(4x^2-5x) : 2x + (2x)^2`
`=4x (2x^2-x) : 4x - 2x(2x-5/2 ) :2x + 4x^2`
`=2x^2-x-2x+5/2+4x^2`
`=6x^2-3x+5/2`
b, `(3x^3-x^2y) :x^2 -(xy^2+x^2y) :xy + 2x(x+1)`
`=x^2 (3x-y) :x^2 -xy(y+x) + (2x^2+2x)`
`=3x-y-y-x+2x^2+2x`
`=2x^2+4x-2y`
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(=16x^2-56x\)
b) \(=161x^3+184x^2-207x\)
c) \(=7x^3y^2+28x^2y^3-7x^2y^2+7xy^3\)
d) \(=-5x^3+10x^2+5x\)
Ai giúp với ạ TvT mình đang cần gấp~
y=6 ; x=3